Resultados del Índice de Progreso Social Mundial 2022 - Marquina, Percy (2022)
37 Páginas / http://centrum.pucp.edu.pe / https://centrumthink.pucp.edu.pe / Editora: Aída del Rocío Vega Salas aida.vega@pucp.pe